Antibiotic Use and Resistance for Beef Cattle Producers - Chad Carr; Matthew J. Hersom; K. C. Jeong; Nicolas DiLorenzo; Jason M. Scheffler; Gina Faniola; Stephanie Miller; Haley Denney; Victoria Roberts; Nahilia Williams; Bianca McCracken (EDIS)
Antibiotic-resistant microorganisms cause millions of illnesses and cost billions of dollars in the United States each year. This 5-page fact sheet written by Chad Carr, Matt Hersom, K. C. Jeong, Nicolas DiLorenzo, Jason Scheffler, Victoria Roberts, Gina Faniola, Stephanie Miller, Haley Denney, Nahilia Williams, and Bianca McCracken and published by the UF/IFAS Department of Animal Sciences discusses the use of antibiotics in cattle production operations and answers some common questions about antibiotics and antibiotic-resistant microorganisms. http://edis.ifas.ufl.edu/an351